The myosin cross-bridge cycle and its control by twitchin phosphorylation in catch muscle. - Butler, T M (2001)
The anterior byssus retractor muscle of Mytilus edulis was used to characterize the myosin cross-bridge during catch, a state of tonic force maintenance with a very low rate of energy utilization. Addition of MgATP to permeabilized muscles in high force rigor at pCa > 8 results in a rapid loss of some force followed by a very slow rate of relaxation that is characteristic of catch. The fast component is slowed 3-4-fold in the presence of 1 mM MgADP, but the distribution between the fast and slow (catch) components is not dependent on [MgADP]. Phosphorylation of twitchin results in loss of the catch component. Fewer than 4% of the myosin heads have ADP bound in rigor, and the time course (0.2-10 s) of ADP formation following release of ATP from caged ATP is similar whether or not twitchin is phosphorylated. This suggests that MgATP binding to the cross-bridge and subsequent splitting are independent of twitchin phosphorylation, but detachment occurs only if twitchin is phosphorylated. A similar dependence of detachment on twitchin phosphorylation is seen with AMP-PNP and ATPgammaS. Single turnover experiments on bound ADP suggest an increase in the rate of release of ADP from the cross-bridge when catch is released by phosphorylation of twitchin. Low [Ca(2+)] and unphosphorylated twitchin appear to cause catch by 1) markedly slowing ADP release from attached cross-bridges and 2) preventing detachment following ATP binding to the rigor cross-bridge.